2012
DOI: 10.2164/jandrol.112.016667
|View full text |Cite
|
Sign up to set email alerts
|

Erectile Dysfunction and Extramarital Sex Induced by Timed Intercourse: A Prospective Study of 439 Men

Abstract: During the fertile window of a woman's menstrual cycle, the effect of impending timed intercourse (TI) on the psychological well-being and behavior of male partners has not been thoroughly investigated, despite the fact that men comprise one half of each couple endeavoring to achieve natural conception. This prospective study consisting of 439 men was conducted during a 3-year period between July 1, 2008, and June 30, 2011. Various characteristics were evaluated, including newly acquired erectile dysfunction (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 43 publications
0
15
0
Order By: Relevance
“…Table 1 summarizes the ED and DE incidences by TI frequency. Table 2 shows the BAI and BPAQ scores of our study cohort, and Table S1 shows the basic characteristics of the men with ( n = 188) and without ( n = 251) ED as reported in a previous paper [13]. The LH, testosterone and E2 levels differed significantly between the two groups ( P = 0.013, 0.004 and <0.001, respectively).…”
Section: Resultsmentioning
confidence: 81%
See 2 more Smart Citations
“…Table 1 summarizes the ED and DE incidences by TI frequency. Table 2 shows the BAI and BPAQ scores of our study cohort, and Table S1 shows the basic characteristics of the men with ( n = 188) and without ( n = 251) ED as reported in a previous paper [13]. The LH, testosterone and E2 levels differed significantly between the two groups ( P = 0.013, 0.004 and <0.001, respectively).…”
Section: Resultsmentioning
confidence: 81%
“…A 7%–15% ED prevalence has been reported among adults in Asian studies [15]. The ED details of our study participants have been fully discussed in a previous paper [13]. In this study, we focused on the responses to tadalafil treatment and BAI and BPAQ scores of the men with TI‐related ED.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Incorrect timing of intercourse may affect a couple's ability to conceive, but timed intercourse (TI) may associate with adverse aspects. For example, the study showed that as the number of TI episodes increased, the number of men with erectile dysfunction and extramarital sex and those who wanted to avoid TI also increased [4]. The effect of TI on the female sexual function has not been thoroughly investigated.…”
Section: Introductionmentioning
confidence: 99%
“…A high risk of bias was found in three of the studies due to recruitment difficulties, incomplete outcome data and involvement of the manufacturer of the ovulation detection method, with all studies likely to suffer from a bias in self‐reported pregnancy due to the impossibility of blinding . Furthermore, recent research on the impact of timed intercourse on men suggests the practice may increase the likelihood of negative outcomes such as erectile dysfunction and extra‐marital relationships . Only one other study evaluated possible harm through recommending urinary test kits, finding no difference in the subjective stress measures over the course of two menstrual cycles among 210 women trying to conceive.…”
Section: Discussionmentioning
confidence: 99%